Pengaruh Supervisi Terhadap Kinerja Guru Taman Kanak-Kanak Di Kecamatan Baleendah Berdasarkan Tingkat Akreditasi - Afriyani Shafira, Nanda; Rahman, Taopik; Sianturi, Risbon (Ar-Raihanah: Jurnal Pendidikan Islam Anak Usia Dini, 2025)
This This study aims to examine the influence of principal supervision on kindergarten teacher performance in Baleendah District, and to determine whether there are performance differences based on school accreditation levels. A quantitative approach was used with 82 teacher participants from 20 kindergartens accredited at levels A, B, and C. Data were collected through a closed-ended questionnaire and analyzed using simple linear regression and one-way ANOVA. The results indicate that supervision significantly influences teacher performance, while no significant differences were found based on accreditation level. These findings highlight the importance of supervision quality over institutional status. The study recommends implementing reflective and participatory supervision to sustainably improve teacher performance